Secure resource allocation and scheduling for OFDMA decode-and-forward relay networks - Ng, Derrick Wing Kwan; Lo, Ernest S.; Schober, Robert (IEEE Transactions on Wireless Communications, 2011)
In this paper, we formulate an optimization problem for secure resource allocation and scheduling in orthogonal frequency division multiple access (OFDMA) half-duplex decode-and-forward (DF) relay assisted networks. Our problem formulation takes into account artificial noise generation to combat a passive multiple antenna eavesdropper and the effects of imperfect channel state information at the transmitter (CSIT) in slow fading. The optimization problem is solved by dual decomposition which results in a highly scalable distributed iterative resource allocation algorithm. The packet data rate, secrecy data rate, power, and subcarrier allocation policies are optimized to maximize the average secrecy outage capacity (bit/s/Hz securely and successfully delivered to the users via relays). Simulation results illustrate that our proposed distributed iterative algorithm converges to the optimal solution in a small number of iterations and guarantees a non-zero secrecy data rate for given target secrecy outage and channel outage probability requirements. © 2011 IEEE.
CRIS-Team Scopus Importer:2020-02-03
Keywords: artificial noise generation; decode-and-forward relay; imperfect CSI; MIMO beamforming; passive eavesdropper; Physical (PHY) layer security